Recurrent esophageal adenocarcinoma derived from ectopic gastric mucosa: A case report. Issue 6 (1st February 2022) - Kitasaki, Nao; Hamai, Yoichi; Yoshikawa, Toru; Emi, Manabu; Kurokawa, Tomoaki; Hirohata, Ryosuke; Ohsawa, Manato; Okada, Morihito
Abstract: Most primary esophageal adenocarcinomas arise from the Barrett epithelium of the distal esophagus. Thus, cancer developing from the ectopic gastric mucosa (EGM) of the proximal esophagus is extremely rare. Furthermore, recurrent adenocarcinoma at the EGM has not been reported. Here, we describe adenocarcinoma originating from the EGM at the boundary of the cervical and thoracic esophagus that recurred twice at the same site within 40 months. This adenocarcinoma was treated throughout its course by three endoscopic submucosal dissections and a subsequent thoracoscopic esophagectomy. This is the first description of recurrent adenocarcinoma originating from the EGM of the proximal esophagus. Abstract : We describe adenocarcinoma originating from the ectopic gastric mucosa (EGM) at the boundary of the cervical and thoracic esophagus that recurred twice at the same site within 40 months. This adenocarcinoma was treated throughout its course by three endoscopic submucosal dissections and a subsequent thoracoscopic esophagectomy. This is the first description of recurrent adenocarcinoma originating from the EGM of the proximal esophagus.